Evaluation of acquisition of comprehension skills according to whole brain model - Sarikaya, Bünyamin; Söylemez, Y. (Horizon Research Publishing, 2018)
The aim of this study is to analyze the acquisition of comprehension skills according to the Whole Brain Model. The 50 listening and reading skills in the 2018 Turkish language teaching curriculum were examined. The study was based on qualitative research method. Data were collected using a document review and a structured and an unstructured interview form. Data were analyzed using descriptive analysis method. When necessary, reassessment was made and data were collected and reanalyzed and a comprehensive and complementary study report was prepared. While determining which brain area(s) those listening and reading skills are associated with, researchers independently codified to achieve cross-form reliability (82%) and prepared the first draft. This draft was reviewed by 35 experts in the fields of Turkish Education, Turkish Language and Literature Education, Educational Sciences and Medicine. Experts were asked to evaluate the compliance of the items on a scale of 1 to 10. The final draft was submitted to 12 experts in the fields of Turkish Education, Educational Sciences and Medicine who did not participate in the study before in order to establish content validity. The final decision on items with a score of less than 80% and a CVR lower than .56 was reached by conducting group discussions in line with expert opinion. According to the Whole Brain Model, 12 out of 15 listening/watching skills are associated with the upper left quadrant, 9 with the lower left quadrant and 10 with the upper right quadrant. Only 1 skill is associated with the lower right quadrant. Out of 35 reading skills, 24, 23 and 21 are associated with the upper left, lower left and upper right quadrants, respectively. Only 3 skills are associated with the lower right quadrant. These results indicate that the 2018 Turkish language teaching curriculum does not include sufficient number of skills associated with all quadrants. It is recommended that these results be taken into account when preparing the next curriculum and integrating skills into it. © 2018 by authors, all rights reserved.
Keywords: Acquisition; Brain; Whole Brain Model